The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2732501620974578
|View full text |Cite
|
Sign up to set email alerts
|

Filling the Void: Use of the Interpositional Buccal Fat Pad to Decrease Palatal Contraction and Fistula Formation

Abstract: Objective: The objective of this study was to evaluate the ability of the buccal fat pad flap (BFPF) to fill the void remaining after muscle transposition and study its effect on durability, fistula rate, palatal shortening/contraction, and relapse of muscle positioning in wide and challenging cleft repairs. Design: A retrospective chart review was performed. Charts were abstracted for standard demographics, reason for BFPF utilization, palatal length, palatal fistula, co-morbidities, and speech outcomes. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Our retrospective analysis of the 6-month complication rate revealed that this modified Furlow double-opposing Z-plasty palatoplasty with the 3-layer repair of the hard and soft palates resulted in adequate cleft palate closure with rapid mucosalization of lateral relaxing incisions and no wound separation or fistula formation. This corroborates published data of satisfactory palatal healing status with reduced fistula rates following the use of pedicled buccal fat flaps in Furlow palatoplasties (Levi et al, 2009; Bennett et al, 2017; Qiu et al, 2019; Horswell and Chou, 2020; Kim et al, 2020; Thurston et al, 2020; Denadai and Lo, 2021). Interestingly, recent comparative investigations have demonstrated that adding buccal fat flaps in Furlow double-opposing Z-plasty palatoplasty improves the postoperative palatal length (Kotlarek et al, 2021a) and transverse maxillary development (Lo et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our retrospective analysis of the 6-month complication rate revealed that this modified Furlow double-opposing Z-plasty palatoplasty with the 3-layer repair of the hard and soft palates resulted in adequate cleft palate closure with rapid mucosalization of lateral relaxing incisions and no wound separation or fistula formation. This corroborates published data of satisfactory palatal healing status with reduced fistula rates following the use of pedicled buccal fat flaps in Furlow palatoplasties (Levi et al, 2009; Bennett et al, 2017; Qiu et al, 2019; Horswell and Chou, 2020; Kim et al, 2020; Thurston et al, 2020; Denadai and Lo, 2021). Interestingly, recent comparative investigations have demonstrated that adding buccal fat flaps in Furlow double-opposing Z-plasty palatoplasty improves the postoperative palatal length (Kotlarek et al, 2021a) and transverse maxillary development (Lo et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, recent comparative investigations have demonstrated that adding buccal fat flaps in Furlow double-opposing Z-plasty palatoplasty improves the postoperative palatal length (Kotlarek et al, 2021a) and transverse maxillary development (Lo et al, 2021). Based on the existing objective data (Thurston et al, 2020; Lo et al, 2021; Kotlarek et al, 2021a), we hypothesized that this modified palatoplasty technique could not only reduce the wound dehiscence and fistula formation for early postoperative outcomes but also achieve a satisfactory speech outcome and reduce the probable negative influence on transverse maxillary arch development and midfacial growth. However, the potential benefit of enhanced muscle sling functioning due to less fibrotic tissue formation and prevention of maxillary growth disturbance by reducing scar contraction remains theoretical, as our 6-month follow-up interval restricts any conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different groups have incorporated buccal fat pad flaps into double-opposing Z-plasty palatoplasty. [8][9][10][11][12][13][14][15][16] Technically, it adds 10 to 15 minutes Plastic and Reconstructive Surgery • January 2022 to the operative time, 8,10 with minimal facial aesthetic impact or compromise of facial symmetry in the donor-site region. 19,20 In this study, split buccal fat flaps were adopted to decrease the risk of postoperative fistula formation and palatal contraction and to reduce bone exposure during the healing process.…”
Section: Discussionmentioning
confidence: 99%